Outsourcing in the new strategy of multinational companies:foreign investment, international subcontracting and production relocation. - Andreff, Wladimir (Papeles de Europa, 2009)
The article is dealing in the first place with the definition of (offshore) outsourcing in relation with foreign direct investment and international subcontracting process, as well as with some connected issues such as fragmentation of the production process, international production relocation, de-industrialisation in developed countries and industrialisation in newly industrialising, now coined emerging countries. In the second place, it aims at finding how global strategy differentiates from traditional MNC strategies and how much outsourcing fits with such global strategy. The last section of the article briefly screens the economic impact of outsourcing on the world trade structure – with the two enlightening snapshots of global trade in sports goods and European Union 15’s outward processing trade with Central Eastern European countries (CEECs)-, as well as on home developed and host emerging countries. The article conclusion is that outsourcing has grown faster than world trade in the past two decades and has skyrocketed during the very last years because it is a cornerstone of a new global strategy adopted by multinational companies since the late 1980s.